1997
DOI: 10.1016/s0009-9236(97)90031-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of the CYP2C subfamily and its effect on the pharmacokinetics of phenytoin in Japanese patients with epilepsy*

Abstract: The findings indicated that the genetic polymorphisms of CYP2C isozymes play an important role in the pharmacokinetic variability of phenytoin and that the mutation in CYP2C9 proteins (Ile359-->Leu) is a determinant of impaired metabolism of the drug among Japanese persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
83
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(87 citation statements)
references
References 13 publications
4
83
0
Order By: Relevance
“…For several CYP2C9 substrates, metabolism by the CYP2C9.3 enzyme variant is markedly reduced compared to the enzyme encoded by CYP2C9 * 1 [6,8,9] . This has clinical implications for CYP2C9 drugs with narrow therapeutic windows, such as warfarin and phenytoin, where drug accumulation due to slow metabolism will increase the risk of severe adverse reactions [10][11][12]. The primary objective of the present study was to assess the impact of CYP2C9 polymorphism on celecoxib oxidation in vitro , and to characterize further the enzymatic steps involved in the formation of carboxycelecoxib.…”
Section: Introductionmentioning
confidence: 99%
“…For several CYP2C9 substrates, metabolism by the CYP2C9.3 enzyme variant is markedly reduced compared to the enzyme encoded by CYP2C9 * 1 [6,8,9] . This has clinical implications for CYP2C9 drugs with narrow therapeutic windows, such as warfarin and phenytoin, where drug accumulation due to slow metabolism will increase the risk of severe adverse reactions [10][11][12]. The primary objective of the present study was to assess the impact of CYP2C9 polymorphism on celecoxib oxidation in vitro , and to characterize further the enzymatic steps involved in the formation of carboxycelecoxib.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variation in the CYP2C9 gene can affect metabolism, leading to altered phenotypes. Individuals with poor metaboliser alleles of CYP2C9 gene were shown to have a reduced metabolism of phenobarbital, phenytoin and valproate compared with those with wild-type (normal) alleles [2][3][4][5][6][7][8][9] . Several studies indicate that the most common allelic variants are Arg 144 Cys (CYP2C9*2) and Ile 358 Leu (CYP2C9*3) which encode enzymes with decreased substrate turnover 10,11 .…”
mentioning
confidence: 99%
“…On the other hand, previous in vivo studies showed that individuals who were genotyped as CYP2C9*3 reduced the clearance of S-warfarin, tolbutamide and phenytoin. [6][7][8] Also, expression systems of CYP enzymes have been used to investigate the catalytic activities of the enzymes in vitro, and the Leu 359 variant significantly affected the kinetic parameters in vitro, such as S-warfarin, 9 tolbutamide 7 and torsemide. 10 However, there has been no study on the CYP2C9 catalytic property of candesartan.…”
Section: Introductionmentioning
confidence: 99%